Stellarex Drug-Coated Balloon for Treatment of Femoropopliteal Disease: Twelve-Month Outcomes From the Randomized ILLUMENATE Pivotal and Pharmacokinetic Studies. Issue 12 (19th September 2017) - Krishnan, Prakash; Faries, Peter; Niazi, Khusrow; Jain, Ash; Sachar, Ravish; Bachinsky, William B.; Cardenas, Joseph; Werner, Martin; Brodmann, Marianne; Mustapha, J. A.; Mena-Hurtado, Carlos; Jaff, Michael R.; et al.
Abstract : Background: Drug-coated balloons (DCBs) are a predominant revascularization therapy for symptomatic femoropopliteal artery disease. Because of the differences in excipients, paclitaxel dose, and coating morphologies, varying clinical outcomes have been observed with different DCBs. We report the results of 2 studies investigating the pharmacokinetic and clinical outcomes of a new DCB to treat femoropopliteal disease. Methods: In the ILLUMENATE Pivotal Study (Prospective, Randomized, Single-Blind, U.S. Multi-Center Study to Evaluate Treatment of Obstructive Superficial Femoral Artery or Popliteal Lesions With A Novel Paclitaxel-Coated Percutaneous Angioplasty Balloon), 300 symptomatic patients (Rutherford class 2–4) were randomly assigned to DCB (n=200) or standard angioplasty (percutaneous transluminal angioplasty [PTA]) (n=100). The primary safety end point was freedom from device- and procedure-related death through 30 days, and freedom from target limb major amputation and clinically driven target lesion revascularization through 12 months. The primary effectiveness end point was primary patency through 12 months. In the ILLUMENATE PK study (Pharmacokinetic Study of the Stellarex Drug-Coated Angioplasty Balloon), paclitaxel plasma concentrations were measured after last DCB deployment and at prespecified times (at 1, 4, 24 hours and at 7 and 14 days postprocedure) until no longer detectable. Results: In the ILLUMENATE Pivotal Study, baseline characteristics were similar between groups: 50% had diabetes mellitus, 41% were women, mean lesion length was 8.3 cm, and 44% were severely calcified. The primary safety end point was met (92.1% for DCB versus 83.2% for PTA, P =0.025 for superiority) and the primary patency rate was significantly higher with DCB (76.3% for DCB versus 57.6% for PTA, P =0.003). Primary patency per Kaplan-Meier estimates at day 365 was 82.3% for DCB versus 70.9% for PTA ( P =0.002). The rate of clinically driven target lesion revascularization was significantly lower in the DCB cohort (7.9% versus 16.8%, P =0.023). Improvements in ankle-brachial index, Rutherford class, and quality of life were comparable, but the PTA cohort required twice as many revascularizations. Pharmacokinetic outcomes showed that all patients had detectable paclitaxel levels after DCB deployment that declined within the first hour (54.4±116.9 ng/mL to 1.4±1.0 ng/mL). Conclusions: The data demonstrate superior safety and effectiveness of the Stellarex DCB in comparison with PTA, and plasma levels of paclitaxel fall to low levels within 1 hour. Clinical Trial Registration: URL:http://clinicaltrials.gov . Unique identifiers: NCT01858428 and NCT01912937. Abstract : Supplemental Digital Content is available in the text.